Tissue Banking: Relationship with Blood Donor and Organ Donor Card Status. (5th March 2012) - McKenzie, Kenneth D.; Fitzpatrick, Patricia E.; Sheehan, John D.
Abstract : Understanding the relationships among altruistic health acts may serve to aid therapeutic research advances. In this paper, we report on the links between two such behaviours—donating blood and carrying an organ donor card—and willingness to donate urological tissue to a tissue bank. Reasons for the differential willingness to do so are examined in this paper. A systematic sample of 259 new and returning attendees at a tertiary urology referral clinic in Ireland completed a self-report questionnaire in an outpatient setting. In addition to demographic details, details of known diagnosis of malignancy and family history of cancer; attitudes to tissue donation for research purposes were gauged using a 5-point Likert scale. Both blood donors and organ donor card carriers were more likely to be willing to donate tissue for research purposes. Blood donors were more likely want to know their overall results in comparison to nonblood donors and want their samples to be used for nonprofit research. Our hypothesis that being a blood donor would be a better predictor to donate urological tissue than being an organ donor card carrier borne out by the trends reported above.